Sea Surface Temperature Of Manado Bay and Its Surroundings - Paruntu, Kheren Patrisia; Rampengan, Royke M; Manengkey, Hermanto W. K; Mamuaya, Jane M; Windarto, Agung B; Moningkey, Ruddy D (Jurnal Ilmiah Platax, 2021)
Indonesia is a maritime country where as much as two-thirds of its territory is the ocean. The waters of Manado Bay and its surroundings which are located in North Sulawesi Province are waters with great potential. Bunaken National Park, which is an important tourist destination in Indonesia, is situated in Manado Bay. Sea surface temperature (SST) is an important factor that influences climate dynamics and also the life of marine organisms. The information regarding SST is needed not only on a local scale but also globally. SST is a key variable that underpins weather predictions, ocean forecasts, and ocean-atmospheric variability leading to the understanding and forecasting of short- and long-term climate variability. This study was conducted with the aim of describing and analyzing daily and seasonal SST in several places in the waters of Manado Bay and its surroundings. The study was conducted by using data from the Copernicus Marine Environment Monitoring Service (CMEMS), which is a global marine data provider institution. This digital data have scientific qualifications and is updated regularly. CMEMS provides maps and data for forecasting oceanographic conditions. Based on the study conducted, it was found that in 2020 the SST at the research location was varied according to the time and station determined. The highest SST in Manado Bay and the surrounding waters generally occurs around May, although the values are not exactly the same. The lowest SST value varies by station, but the value can be at a temperature slightly below 28oC and occurs around February to April.Keywords : SST; Manado Bay; Bunaken Island; CMEMSAbstrak Indonesia merupakan Negara maritim di mana sebanyak dua per tiga wilayah Indonesia adalah laut. Perairan Teluk Manado dan sekitarnya yang terletak di Provinsi Sulawesi Utara merupakan salah satu perairan yang sangat potensial. Taman Nasional  Bunaken yang menjadi tempat tujuan wisata yang penting di Indonesia.  Suhu permukaan laut (SPL) merupakan faktor penting yang mempengaruhi dinamika iklim dan juga kehidupan organisme laut. Kepentingan terhadap informasi menyangkut SPL dibutuhkan bukan hanya pada skala lokal, tetapi juga global.  SPL adalah variabel kunci yang mendukung prediksi cuaca, prakiraan laut, dan variabilitas atmosfer laut yang mengarah pada pemahaman dan prakiraan variabilitas iklim jangka pendek dan jangka panjang. Penelitian ini dilakukan dengan tujuan mendeskripsikan dan menganalisis SPL harian dan musiman di beberapa tempat pada kawasan perairan Teluk Manado dan sekitarnya.  Kajian dilakukan menggunakan data Copernicus Marine Environment Monitoring Service (CMEMS) yang adalah suatu lembaga penyedia data kelautan global.  Data digital ini memiliki kualifikasi ilmiah dan diperbarui secara berkala. CMEMS menyediakan  peta dan data  untuk prakiraan kondisi oseanografi. Berdasarkan kajian yang dilakukan, selama tahun 2020 SPL pada lokasi penelitian berada pada kisaran yang berbeda menurut waktu maupun stasiun yang ditetapkan. SPL tertinggi Teluk Manado dan perairan sekitarnya umumnya terjadi pada sekitar bulan Mei, walaupun dengan nilai yang tidak persis sama. Nilai SPL terendah berbeda menurut stasiun, tetapi nilainya bisa berada pada suhu sedikit di bawah 28oC dan terjadi pada sekitar bulan Februari sampai April.